Sea level pressure variation and major cyclone events in coastal regions of Bangladesh (Progressive Agriculture, 2016)
The study was conducted in 16 coastal district viz. Satkhira, Khulna, Mongla, Khepupara, Barishal, Bhola, Patuakhali, Hatiya, Chandpur, Feni, Swandip, Sitakunda, Chittagong, Kutubdia, Coxs Bazar and Teknaf of Bangladesh during the period of 1975-2014 to investigate the variation of sea level pressure (SLP) and rainfall. SLP data of 40 years (1975-2014) have been analyzed in this study. The SLP was increasing slightly to the month of September and then a rapid increasing was observed from the month of October to December. Of all the stations, in the month of June and July the lowest SLP was observed in the Khulna region and highest in Teknaf. In the month of December and January the highest and lowest SLP was found in the Month of January. As the fluctuation of SLP was high in the summer season the possibility of cyclone occurrence also rise in this season. The average rainfall is lowest in the station Sitakunda and highest in Swandip. The average rainfall of all district divided the stations into two parts. The rainfall of Barishal, Bhola, Chandpur, Mongla, Sitakunda and Khulna is lower the average of all district. This shows a great instability of weather in these regions. Rest of the stations has the higher average rainfall than the average rainfall of all stations.Progressive Agriculture 27 (3): 285-295, 2016